Hydrophobically modified poly(acrylic acid) using 3-pentadecylcyclohexylamine: synthesis and rheology - Shedge, A. S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique; Pcrrin, P.; Chassenieux, Christophe; Badiger, Manohar V. (Macromolecular Chemistry and Physics, 2005)
Hydrophobically modified poly(acrylic acid) was synthesized using 3-pentadecylcyclohexylamine (3-PDCA), which was in turn synthesized from 3-pentadecylphenol, one of the components of cashew-nut shell liquid (CNSL), a renewable resource material. H-1 NMR spectra confirmed the incorporation of 3-PDCA onto PAA and a series of HMPs with three different molar concentrations, viz. congruent to 3, 5 and 7 mol-% of 3-PDCA, were synthesized. An increase in viscosity with increasing hydrophobic content was observed by rheological measurements. The critical association concentrations were determined using an Ubbelohde viscometer and a controlled stress rheometer. The stability of HMPs towards temperature and shear was studied. Rheological measurements showed that there was a steady increase in viscosity with increase in hydrophobe content due to the formation of reversible networks. These polymers exhibited gel-like behavior at low concentrations (greater than or equal to2 wt.-%) with an apparent yield stress (ca. 10 Pa) and showed shear thinning properties (non-Newtonian). However, below a critical concentration, c [eta], they showed Newtonian behavior.
Keywords: 3-pentadecylcyclohexylamine (3-PDCA); hydrophobically modified polymers (HMPs); poly(acrylic acid); reversible associations; Rheology

Studies on shrikhand rheology - Kulkarni, C.; Belsare, N.; Lele, Ashish K. (Journal of Food Engineering, 2006)
Shrikhand, a popular Indian dessert made from yogurt, is manufactured on an industrial scale using several chemical engineering unit operations such as mixing, filtration and heat transfer. Understanding the rheology of shrikhand is not only relevant for designing large scale mixers but can also provide quantitative means for linking the microstructure of shrikhand to its perception of texture, consistency and taste. We show here that shrikhand exhibits a combination of several rheological properties such as weak gel-like viscoelasticity, an apparent yield stress, thixotropy and long structural recovery time scales. For instance, the elastic modulus is always higher than the loss modulus over the measurable frequency range and that both moduli show only weak frequency dependence that is a characteristic of gel-like consistency. Forward and reverse rate sweep tests show a distinct hysteresis loop, which is a signature of thixotropic character. In an attempt to trace the origins of these rheological properties in shrikhand we characterized its microstructure and showed that there exist two different microstructures: one composed of crystallites of milk fats having a length scale of similar to 50-100 mu m, and the other composed of aggregates of colloidal cascin micelles of similar to 0.5-10 mu m size. Our studies show that while the temperature sensitivity of the viscoelastic parameters is dominated by the semicrystalline milk fat microstructure, the shear sensitivity is largely dictated by the protein network. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Microstructure; Rheology; shrikhand

Gelation of regenerated fibroin solution - Nagarkara, Shailesh; Lele, Ashish K.; Chassenieux, Christophe; Nicolai, Taco; Durand, Dominique (15th International Congress on Rheology/80th Annual Meeting of the Society-of-Rheology, 2008)
Silk fibroin is a high molecular weight multiblock ampiphillic protein known for its ability to form high strength fibers. It is also biocompatible; silk sutures have been traditionally used for many centuries. Recently, there has been much interest in making silk hydrogels for applications ranging from tissue engineering to controlled delivery. Fibroin gels can be formed from aqueous solutions by changing one or more state variables such as pH, temperature and ionic strength. In this work we present our investigations on the gelation of aqueous fibroin solutions derived from Bombyx Mori silk using light scattering, confocal microscopy and rheological techniques.
15th International Congress on Rheology/80th Annual Meeting of the Society-of-Rheology, Monterey, CA, AUG 03-08, 2008
Keywords: dynamic light scattering; Rheology; silk fibroin gel

Reactive extrusion of poly(L-Lactic Acid) with glycidol - Deenadayalan, E.; Lele, Ashish K.; Balasubramanian, M. (Journal of Applied Polymer Science, 2009)
Glycidol modified polylactic acid (PLLA) polymers have been prepared by reactive extrusion. Influences of residence time and the concentration of glycidol on the extent of reaction with different weight average molecular weight (45,000, 65,000, and 100,000) PLLA's were studied. Structure-property relationship has been established by measuring molecular, mesoscopic, and macroscopic properties. Under reactive extrusion conditions glycidol reacted with the end groups of PLLA to initiate chain extension. Low-molecular weight PLLA reacted with glycidol faster than the medium molecular weight PLLA, whereas high-molecular weight PLLA did not show significant reactions. The glass transition temperature, melting temperature, crystallization temperature, and heat of fusion were measured for unmodified and modified PLLA's. Chain extended PLLA had higher T(g) and T(m) than the unmodified samples. Time sweep rheological experiments were performed to test the melt stability of PLLA. Chain extended PLLA's were found to retain viscoelastic properties for much longer time than the unreacted samples. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 1391-1398, 2009
Keywords: biodegradable; reactive extrusion; Rheology; structure-property relations; Thermal properties

Hydrophobically modified poly(vinyl alcohol) using alkoxy-substituted methyl gallate: synthesis and rheology - Shedge, Aarti S.; Wadgaonkar, Prakash P.; Lele, Ashish K.; Badiger, Manohar V. (Journal of Polymer Science Part B-Polymer Physics, 2010)
Hydrophobically modified poly(vinyl alcohol) (HMPVA) polymers were synthesized by potassium t-butoxide-catalyzed reaction of PVA with methyl 3,4,5-tris(n-octyloxy) benzoate (MGC(8))/3,4,5-tris(n-dodecyloxy) benzoate (MGC(12)) and 1,3-propane sultone. The concentration of 1,3-propane sultone was kept constant at 10 mol %. and that of MGC(8) (2, 3, and 4 mol %)/MGC(12) (2 and 3 mol %) was varied to obtain HMPVAs with different hydrophobic contents. The incorporation of MGC(8)/MGC(12) and 1,3-propane sultone onto HMPVA was confirmed by NMR spectroscopy. Rheological properties of aqueous solutions also confirmed the presence of hydrophobic and charged functional groups on HMPVAs. In the semidilute regime, the specific viscosity of HMPVAs followed concentration scaling that is typical of polyelectrolytes. At higher concentrations, the HMPVA solutions with 3 and 4 mol % of MGC(8) exhibited large increase in specific viscosity. Oscillatory experiments on these solutions exhibited gel-like behavior at polymer concentrations of 40-50 g/L. Confocal microscopy images of HMPVA with 4 mol % of MGC(8) clearly indicated the existence of microgels. The tendency of formation of microgels further increased with increasing chain length of the hydrophobe, that is, with MGC(12). These samples exhibited rheological behavior that is typical of soft solids and was therefore probed by the strain-rate frequency superposition technique reported recently in the literature. HMPVAs with improved rheological properties show potential applications as thickeners in cosmetic creams, lotions and as drug carriers in pharmaceutical formulations. (C) 2010 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 48: 1054-1063, 2010
Keywords: gallic acid; hydrophobically modified poly(vinyl alcohol); Rheology; water-soluble polymers

Influence of reactive compatibilization on the structure and properties of PP/LDH nanocomposites - Lonkar, Sunil P.; Therias, Sandrine; Leroux, Fabrice; Gardette, Jean Luc; Singh, Raj Pal (Polymer International, 2011)
Polypropylene (PP)/layered double hydroxide (LDH) nanocomposites were prepared by the direct melt intercalation method usingmaleic anhydride grafted polypropylene (PP-g-MAH) as a reactive compatibilizer. The compatibilization effects provided by PP-g-MAH in different weight fractions and their influence on the structure and properties of the final nanocomposites were investigated. The interactions and structural morphology of the nanocomposites were examined by Fourier transform infrared spectroscopy, X-ray diffraction and transmission electronmicroscopy. Thermal, mechanical and rheological properties of these nanocomposites were investigated as a function of compatibilizer concentration. The detailed morphological and X-ray diffraction results revealed that the degree of LDH dispersion increases as the amount of PP-g-MAH increases. Study of the linear viscoelastic properties showed that the storage modulus G' is very sensitive to the microstructure of the nanocomposite. The thermal properties of the nanocomposites were significantly influenced by the weight fraction of PP-g-MAH due to the shielding and nucleating effect of exfoliated layers. Both the tensile strength and modulus showed substantial improvements with increasing PP-g-MAH content, while the elongation at break substantially decreased, although the presence of PP-gMAH somewhat improves these values. The overall results showed that 10 wt% of compatibilizer is optimum to achieve nanocomposites with better performance. (C) 2011 Society of Chemical Industry
Keywords: compatibilization; layered double hydroxides; Nanocomposites; polypropylene; Rheology; thermomechanical properties

Gellan Gum a novel polysaccharide matrix for immobilization of thermo-tolerant yeast cells with invertase activity: factorial design and rheological studies - Sulabha, Karandikar; Asmita, Prabhune (Research Journal of Biotechnology, 2012)
The microbial extracellular polysaccharide gellan gum has been explored for its application in whole cell immobilization. Preliminary evaluation of the physicochemical properties of gellan gum in the presence of monovalent cation tetramethyl ammonium chloride (TMACl) was carried out. Gellan gum immobilized cells demonstrated better rheological properties than gellan gum. Attempts have been made to reveal the evaluation of gellan gum as a matrix to immobilize a thermotolerant yeast Kluyveromyces marxianus NCYC 2675. A 3(2) factorial design was used to study the simultaneous effect of two variables. The effect of the polymer concentration and TMACl concentration on various dependent variables like gelling temperature, mean particle size and enzyme activity of the yeast cells was studied. A statistical model with a significant interaction term was obtained to predict the results. Further, optimized immobilized system was evaluated with significant storage stability at 10 C and enhanced reusability with maximum conversion of > 90 % when crosslinked with glutaraldehyde.
Keywords: Gellan gum; Glutaraldehyde; Immobilization; invertase; Rheology; yeast cells

Ascertaining universal features of yielding of soft materials - Kamble, Samruddhi; Pandey, Anurag; Rastogi, Sanjay; Lele, Ashish K. (Rheologica Acta, 2013)
Many metastable complex fluids, when subjected to oscillatory shear flow of increasing strain amplitude at constant frequency, are known to show a characteristic nonlinear rheological response which consists of a monotonic decrease in the elastic modulus and a nonmonotonic change in the loss modulus. In particular, the loss modulus increases from its low strain value, crosses the elastic modulus, and then decreases with further increase in the strain amplitude. Miyazaki et al. (Europhys Lett 75:915-921, 2006) proposed a qualitative argument to explain the origin of the nonmonotonic nature of the loss modulus and suggested that in fact this response could be universal to all complex fluids if they are probed in a certain frequency window in which the fluid is dominantly elastic in the small strain limit. In this letter, we confirm their hypothesis by showing that a wide variety of complex fluids, irrespective of their thermodynamic state under quiescent conditions, indeed show the aforementioned characteristic nonlinear response. We also show that the maximum relative dissipation during yielding occurs when the imposed frequency resonates with the characteristic beta relaxation frequency of the fluid.
Keywords: Colloidal suspensions; Entangled melts; Gels; Glasses; Microgels; Rheology; Yielding

Rheology and microstructural studies of regenerated silk fibroin solutions - Nisal, Anuya; Kalelkar, Chirag; Bellare, Jayesh R.; Lele, Ashish K. (Rheologica Acta, 2013)
Regenerated silk fibroin solutions (RSF) are produced by dissolving degummed silk fibers in water. We have observed that RSF solutions at a concentration less than 15 % by weight exhibit an unusual gel-like response in conventional shear rheology measurements. At higher concentrations, the response is predominantly viscous (or liquid-like). We have probed this counterintuitive behavior of silk fibroin solutions by using microrheology, and interfacial rheometry. Scattering techniques were also used to understand the microstructure of RSF solutions as a function of the concentration. Our studies suggest that the gel-like response of the RSF solution may result from the formation of an interfacial film at the air-solution interface, which dominates the bulk rheological response.
Keywords: Interfacial rheology; Microrheology; Rheology; Silk

Synthesis and characterization of PEPO grafted carboxymethyl guar and carboxymethyl tamarind as new thermo-associating polymers - Gupta, Nivika R.; Torris, Arun A. T.; Wadgaonkar, Prakash P.; Rajamohanan, P. R.; Ducouret, Guylaine; Hourdet, Dominique; Creton, Costantino; Badiger, Manohar V. (Carbohydrate Polymers, 2015)
New thermo associating polymers were designed and synthesized by grafting amino terminated poly(ethylene oxide-co-propylene oxide) (PEPO) onto carboxymethyl guar (CMG) and carboxymethyl tamarind (CMT). The grafting was performed by coupling reaction between-NH2 groups of PEPO and -COOH groups of CMG and CMT using water-soluble EDC/NHS as coupling agents. The grafting efficiency and the temperature of thermo-association, T-assoc in the copolymer were studied by NMR spectroscopy. The graft copolymers, CMG-g-PEPO and CMT-g-PEPO exhibited interesting thermo-associating behavior which was evidenced by the detailed rheological and fluorescence measurements. The visco-elastic properties (storage modulus, G'; loss modulus, G'') of the copolymer solutions were investigated using oscillatory shear experiments. The influence of salt and surfactant on the T-assoc was also studied by rheology, where the phenomenon of ``Salting out'' and ``Salting in'' was observed for salt and surfactant, respectively, which can give an easy access to tunable properties of these copolymers. These thermo-associating polymers with biodegradable nature of CMG and CMT can have potential applications as smart injectables in controlled release technology and as thickeners in cosmetics and pharmaceutical formulations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Carboxymethyl tamarind; Pluronics; Rheology; Solution behavior; Thermo-associating polymers

Thermo thickening behavior of MPEG-b-PCL grafted poly(acrylic acid): a molecular insight - Tiwari, Neha (Polymer, 2018)
We report on the synthesis and characterization of a new thermothickening polymer (PAA-g-(MPEG-b-PCL)) based on the grafting of a block copolymer of mono methoxy poly (ethylene glycol)–b-poly (caprolactone) (MPEG-b-PCL) onto poly (acrylic acid) (PAA). Rheological experiments reveal that aqueous solutions of PAA-g-(MPEG-b-PCL) exhibit interesting irreversible thermothickening behavior above a certain polymer concentration and critical temperature. Light scattering experiments show that increasing temperature induces hydrophobic associations and subsequent aggregation leading to gel formation which is irreversible. The mechanism of thermo thickening was examined at the molecular level by NMR methods which indicated unassembled and assembled environments of the MPEG-b-PCL grafts. On heating, interactions between the graft side chains are significantly enhanced and molecular mobility in the assembled microdomains is reduced. The stable well ordered microdomains that are formed on heating are retained on cooling thus, leading to irreversible gelation.
Keywords: Hydrophobically modified poly (acrylic acid); Light scattering; Methoxy polyethylene glycol-b-polycaprolactone (MPEG-b-PCL) copolymer; Rheology; Thermo gelation

Microstructure and yielding of capillary force induced gel - Huprikar, Sameer; Usgaonkar, Saurabh; Lele, Ashish K.; Orpe, Ashish V. (Rheologica Acta, 2020)
We have investigated the rheology and structure of a gel formed from a mixture of non-Brownian particles and two immiscible liquids. The suspension of particles in a liquid undergoes gelation upon the addition of a small content of second, wetting liquid which forms liquid bridges between particles leading to a sample spanning network. The rheology of this gel primarily exhibits a yield stress at low shear rates followed by a linear variation of shear stress at high shear rates. The apparent yield stress extracted from the flow curves increases rapidly with volume fraction of the second liquid before saturation, while it exhibits a monotonic increase with increasing particle concentration. Rescaling of the yield stress curves using suitable shift factors results in an empirical expression for the yield stress showing squared dependence on liquid fraction and a rapid increase with particle fraction above a certain value, both combined in a highly non-linear manner. The microstructural variations with changing secondary liquid content and particle fractions are captured using three-dimensional X-ray tomography technique. The microstructure is observed to show increased local compactness with increased liquid content and increased spatial homogeneity with increased particle fractions. The images from X-ray tomography are analysed to obtain the distributions of particle-particle bonds (coordination number) in the system which serve to explain the observed yield stress behaviour in a qualitative manner.
Keywords: Capillary force; Flow curve; gel; Microstructure; Rheology; Yield stress

Controlling draw resonance during extrusion film casting of nanoclay filled linear low-density polyethylene: an experimental study and numerical linear stability analysis - Rokade, Dhammaraj; Chougale, Sanket; Patil, Prashant; Bhattacharjee, Tanushree; Gawande, Dnyaneshwar; Pol, Harshawardhan; Dhadwal, Renu (Journal of Plastic Film & Sheeting, 2021)
Commercially important extrusion film casting (EFC) processes for manufacturing plastic films or sheets are hampered by several instabilities that severely limits their productivity. In this research we focussed on one important instability: the draw resonance that occurs during the EFC process mainly under extensional flow conditions. Draw resonance is the sustained periodic oscillations in the film dimensions, notably film width and thickness, when the process operates beyond a critical draw ratio (CDR). In this research our goal was to reduce this draw resonance instability by incorporating well dispersed nanoclay fillers in a base polymeric resin (such as a linear low density polyethylene - LLDPE) to determine how these nanocomposite (NC) formulations can prevent or reduce the draw resonance defect. EFC experiments were conducted on the base resin and on the NC formulations under non-isothermal conditions to determine the onset of the draw resonance experimentally. Conventional linear stability analysis was performed to determine the onset of the draw resonance defect numerically. Numerical predictions for the onset of draw resonance were in qualitative agreement with our experimental data. Our results showed that incorporating appropriate nanoclay concentrations in a base polymeric resin indeed enhanced the EFC process stability for those polymer formulations and thus can have important economic implications for processors.
Keywords: Draw resonance; extensional strain hardening; Extrusion; Film; hydrodynamic interactions; Nanoclay; Nanocomposites; Polyethylene; Rheology; stability

Injectabledextran-fluorenylmethoxycarbonylphenylalanine composite hydrogels with improved mechanical properties - Abraham, Jancy N.; Joseph, Seena; Trivedi, Rishabh; Karle, Mrunal (Polymer International, 2021)
Low molecular weight hydrogels are recently gaining importance owing to their applications in material sciences and biology. A new class of composite hydrogel was developed using polysaccharides such as dextran and fluorenylmethoxycarbonyl phenylalanine (FmocF) in a phosphate buffer. The molecular weight and concentration of the dextran were varied to obtain rigid but injectable hydrogels without using other crosslinking agents. From the different molecular weights of dextran studied (5k, 40k and 70k), a combination of FmocF (0.6% w/v) and dextran 40k (0.012% w/v) composite gels yielded a maximum value of storage modulus of approximately 1500 Pa, which is 3.5 times higher than the storage modulus of pure FmocF gels. Scanning electron microscopy of FmocF/dextran composite gels revealed highly tangled fibrous structures with dense branches and lower fiber diameter compared to pure FmocF gels. The high-intensity hydrogen-bonded N-H peak in the infrared spectra showed enhanced hydrogen bonding in FmocF/dextran composite gels compared to pure FmocF gels. The dextran acts as an impurity in the process of fibrillation, leading to a crystallographic mismatch, and densely packed thin fibers are formed. These gels exhibited gel to sol and sol to gel conversion with temperature or external stress and showed injectable behavior. (c) 2020 Society of Industrial Chemistry
Keywords: Dextran; Fmoc-Phe; hydrogels; injectable gels; Rheology

Investigation of domain structures in monomethoxy poly(ethylene glycol)-b-poly(caprolactone) grafted poly(acrylic acid) by NMR diffusion studies - Tiwari, Neha; Badiger, Manohar Virupax; Rajamohanan, Pattuparambil Ramanpillai; Ravindranathan, Sapna (Polymer International, 2022)
Associating polymers developed by grafting a block copolymer of monomethoxy poly(ethylene glycol)-b-poly(caprolactone) (MPEG-b-PCL) onto poly(acrylic acid) undergo an irreversible sol-gel transition on heating. The influence of various physicochemical parameters on the thermoresponsive behaviour was examined by rheology and NMR studies. Pulsed field gradient NMR diffusion studies were performed to probe the mechanism of thermally induced gelation. Analysis of the diffusion data reveals the presence of loosely and strongly associated structures which respond differently to variation in temperature. It is observed that the polymer solution, which is visibly homogeneous, is heterogeneous on a mesoscopic scale with a distribution of domains. Detailed investigation of the thermally induced sol-gel transition shows that the mechanism of gelation involves irreversible alterations in the domain structure and size. (c) 2022 Society of Industrial Chemistry.
Keywords: associating polymers; hydrophobically modified polymers; NMR diffusion studies; Rheology; sol-gel transition; thermoresponsive polymers

Synthesis of N-oxyethylene substituted imidazolium-based zwitterions as a recyclable solvent for cellulose dissolution - Jadhav, Sachin; Ganvir, Vivek; Singh, Madan Kumar; Shanmuganathan, Kadhiravan (Cellulose, 2023)
Cellulose is a readily available, renewable, and natural biomaterial that has the potential to replace synthetic fibres. However, their processing to shaped materials such as fibre or film is still complex and restricted due to its insolubility in most conventional solvents. Herein, we present the synthesis and cellulose dissolution characteristics of a new class of recyclable zwitterions composed of tethered N-oxyethylene substituted imidazolium cation and alkyl carboxylate anion. Investigations on cellulose dissolution showed that increasing the alkyl chain length of carboxylate anion and introduction of oxyethylene unit on imidazolium ring led to better cellulose dissolution ability, and up to 12% (w/w) cellulose could be dissolved in aqueous zwitterions at 105 degrees C. The thermal behavior of zwitterions and their cellulose solutions was characterized by TGA and found to be more stable than the NMMO and Lyocell solutions. Rheological characterization of cellulose solutions revealed viscoelastic behavior and zero shear viscosity of 6-12% (w/w) cellulose solution in hexanoate containing aqueous zwitterion was 555 to 5900 Pa.s at 120 degrees C. The characteristics of cellulose solution indicate its potential for processing to cellulose fibre by extrusion through a tiny spinneret. Physico-chemical analysis of regenerated cellulose indicates that zwitterions cause no adverse effect on cellulose structure and morphology during dissolution. The zwitterions are recovered after the cellulose regeneration process, and the recovery was found to be 99.6% after purification using the ion-exchange method.
Keywords: Carboxylate anion; Cellulose dissolution; Oxyethylene unit; Regenerated cellulose; Rheology; zwitterions